The EU December Summit Results and Perspectives of Creation of the European Security Council - Igor Shcherbak (Научно-аналитический вестник Института Европы РАН, 2020)
The author analyzed results of the recent EU summit in Brussels and the decisions adopted by it. Special attention has been devoted to the influence of the UK parliamentary elections on the summit which brought perspective of Brexit to the door of the EU. The agenda of the summit contains as well as items related to the convocation of the Conference on future of Europe, the EU budget allocations for 2021–2027, implementation of the decisions of Paris conference on climate changes. It is underlined that combination of two factors – ineffectiveness of present mechanisms of the EU and Brexit – gave relevance to the question of further modernization of the EU with the aim of its consolidation and strengthening the role of the EU in global defense and economy. The article focuses also on creation of the European Security Council (ESC) with the UK participation. It is noted that under certain conditions the idea of association of the UK with a renovated European Un- ion could be attractive to prime-minister B. Johnson striving to revive the global role for the UK. Different variants of formation of the ESC have been considered through a prism of possible adop- tion of this idea by the EU member states. The article contains a forecast concerning the EU further actions on this subject.